BS 7912 AMD 2. Power cables with XLPE insulation and metal sheath, and their accessories, for rated voltages from 66 kV (Um = 72.5 kV) to 132 kV (Um = 145 kV). (7th March 2023) - British Standards Institution,
No abstract available